Indonesian Manuscripts in Great Britain - Ricklefs, Voorhoeve dan Gallop, Annabel Teh (Yayasan Pustaka Obor Indonesia, 2014)
This book is of value not only to scholars of the languages and literatures of maritime Southeast Asia , bus also for studies of the political , economic, social and diplomatix history of the region, the transmission of Islamic thought and the art of the book. Particularly important are the collcetions of manuscript in Malay, Javanese, Batak, Buginese and Makasarese.